1998
DOI: 10.1046/j.1523-1755.1998.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin 1 elicits diverse biologic responses in mesangial cells

Abstract: These data indicate that mesangial cells are susceptible to the effects of Stx1 in vitro. Stx1 exerts a spectrum of biologic effects on mesangial cells ranging from activation of chemokine genes to a lethal toxic injury. Immunoinflammatory cytokines potentiate the effects of Stx1. Thus, glomerular pathology in HUS may also result from a direct effect of Stx1 on mesangial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 43 publications
1
25
0
1
Order By: Relevance
“…These inflammatory mediators have been shown to increase Gb 3 and/or Stx sensitivity in kidney cell types such as mesangium (53), tubular epithelial cells (10), and glomerular microvascular endothelial cells even though TNF-␣ does not affect the retrograde transport of the Stx B subunit in these cells (65). We also show that these cells required minimal times of exposure to LPS or TNF-␣ in order to have increased sensitivity to Stx2.…”
Section: Discussionmentioning
confidence: 62%
“…These inflammatory mediators have been shown to increase Gb 3 and/or Stx sensitivity in kidney cell types such as mesangium (53), tubular epithelial cells (10), and glomerular microvascular endothelial cells even though TNF-␣ does not affect the retrograde transport of the Stx B subunit in these cells (65). We also show that these cells required minimal times of exposure to LPS or TNF-␣ in order to have increased sensitivity to Stx2.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, one model of Stx-mediated disease in mice requires the co-administration of LPS and Stx (50). Several means by which inflammatory cytokines may promote systemic disease have been proposed, including induction of the Gb 3 glycolipid Stx receptor on host cells (89)(90)(91), alteration of fibrinolysis and anticoagulation, or recruitment of inflammatory cells into damaged tissues (77). In response to Stx, cultured monocytes secrete TNF-α and IL-6 (90,92,93), and we found that these cytokines were elevated in the serum or kidneys of mice infected with C. rodentium (λstx 2dact ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inducing TNF-␣, Stx has been shown to induce chemokine production in some types of cells (34,42). For example, Simon et al (30) reported that Stx1 induced monocyte chemoattractant protein 1 production in cultured human mesangial cells. Stx1 also induced the expression of adhesion molecules in endothelial cells (19).…”
Section: Discussionmentioning
confidence: 99%